New Essays by De Quincey : His Contributions to the Edinburgh Saturday Post and the Edinburgh Evening Post - De Quincey, Thomas, 1785-1859 (Book collections on Project MUSE., 1966)
This is the first time these essays have been collected and identified as De Quincey's. Each essay or article is reprinted with full annotation and the author's reasons for attributing it to De Quincey. The essays vary in length and in subject matter: some are addressed to "The Editor"; some are critical reviews of contemporary magazines; some are week-to-week political commentaries on issues facing the second Tory party. Together they show De Quincey, the journalist, working on a variety of subjects that occur in his writing before and after this time, from the financing of empires to an attack on Macaulay or an analysis of Burke's mind and style. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905